The emergence of the "genetic counseling" profession as a counteraction to past eugenic concepts and practices. (10th March 2021) - Zuckerman, Shachar
Abstract: The emergence of the genetic counseling profession has allowed laypeople to understand and benefit from biological advances, and to make critical decisions about their application. The discipline of genetic counseling has been criticized from its very beginning, in particular because of its early association with the eugenics movement. This paper presents a critical and reflective overview of how genetic counseling is implicitly embedded in the history of eugenics but also counteracts past eugenic practices and ideas. After World War II, attempts were made to distance genetic counseling from eugenics. The first definition of genetic counseling did not position this field as a medical encounter but "as a kind of genetic social work aimed primarily to provide people with an understanding of their family's genetics problems." This approach was a reaction to the genetic and social evolutionary ideas that informed eugenic theories during the first half of the 20th century. Professionals engaged in genetic counseling during the 1940s and1950s rejected eugenic practices, but there was still support for eugenics' goals of improving heredity and eliminating disease. From the 1960s, genetic counseling underwent professionalization alongside feminization and a definition of core values. Among these values were nondirectiveness counseling and the autonomy of the counselee. The dark shadow of Nazi ideology and other eugenic practices, attempts to employ the historical responsibility of geneticists, and the dynamic medical, social, political, and educational changes of the 1960s and 1970s helped to frame approaches and delineate the goals and limits of the new profession of "genetic counseling."